Filter bubble - Axel Bruns (Internet Policy Review, 2019)
Introduced by tech entrepreneur and activist Eli Pariser in 2011, the 'filter bubble' is a persistent concept which suggests that search engines and social media, together with their recommendation and personalisation algorithms, are centrally culpable for the societal and ideological polarisation experienced in many countries: we no longer encounter a balanced and healthy information diet, but only see information that targets our established interests and reinforces our existing worldviews. Filter bubbles are seen as critical enablers of Brexit, Trump, Bolsonaro, and other populist political phenomena, and search and social media companies have been criticised for failing to prevent their development. Yet, there is scant empirical evidence for their existence, or for the related concept of 'echo chambers': indeed, search and social media users generally appear to encounter a highly centrist media diet that is, if anything, more diverse than that of non-users. However, the persistent use of these concepts in mainstream media and political debates has now created its own discursive reality that continues to impact materially on societal institutions, media and communication platforms, and ordinary users themselves. This article provides a critical review of the 'filter bubble' idea, and concludes that its persistence has served only to redirect scholarly attention from far more critical areas of enquiry.
Keywords: 300; Filter bubble; Echo chambers; Social media; Social network; Polarisation